Refractive outcomes after DMEK: meta-analysis - Augustin, Victor A.; Son, Hyeck Soo; Yildirim, Timur Mert; Meis, Jan; Łabuz, Grzegorz; Auffarth, Gerd U.; Khoramnia, Ramin (Journal of cataract and refractive surgery, 2023)
In this meta-analysis and systematic literature review of refractive outcomes after Descemet membrane endothelial keratoplasty (DMEK), the extent of the refractive shift and an overview of reasons for refractive shift after DMEK are provided. The PubMed library was screened for articles containing the terms “Descemet membrane endothelial keratoplasty,” “DMEK,” “Descemet membrane endothelial keratoplasty combined with cataract surgery,” “triple-DMEK” combined with “refractive outcomes,” “refractive shift,” and “hyperopic shift.” The refractive outcomes after DMEK were analyzed and compared using a fixed and random effects model. The overall mean change of the spherical equivalent outcome when compared with the preoperative value in cases of DMEK or when compared with the preoperative target refraction in cases of DMEK combined with cataract surgery was +0.43 diopters (D) (95% CI, 0.31-0.55). When DMEK is combined with cataract surgery, a target refraction of −0.5 D is recommended to achieve emmetropia. Changes in the posterior corneal curvature are identified as the main cause of the refractive hyperopic shift.
Gesehen am 28.11.2024